The Role of the Constitutional Court in Safeguarding Democratic Dignity - Junaidin Junaidin; Ahmad Ahmad; Gamal Abdul Nasir; Franky Aryadi; Rijal Ibnu Sani (Indonesian Journal of Law and Policy Studies, 2024)
This article examines the role of the Constitutional Court in maintaining the dignity of democracy. The method used in this research is the Normative Legal research method. The approaches used are the Legislative approach and the Conceptual approach. Constitutional democracy is a political system that affirms that power ultimately originates from the people, yet must be exercised within the limits set by the constitution. Democracy is not simply about five-yearly elections or the majority of votes. It is a system of values that must be maintained through a balance between popular sovereignty and constitutional supremacy. This is where the Constitutional Court (MK) comes into play.the guardian of the constitution at a time the guardian of democracy. Constitutional democracy places the basic law (the constitution) as the guiding principle for democratic practice, ensuring the guarantee of people's rights and preventing abuse of power. Indonesia's constitutional system, following the amendments to the 1945 Constitution, has moved toward constitutional democracy, with direct elections, human rights guarantees, and the strengthening of constitutional guardian institutions. However, democratic practice still faces challenges in the form of political oligarchy, money politics, and limitations in the constitutional courts.